DARE to Say NO - Earls, Anona; Compton, JJ (My University, 2022)
Using the Acronym DARE we'll look specifically at reclassing the offensive and dated terminology of call numbers for materials classified with N and O Cutter numbers for "Negro" and "Oriental." DARE is short for Decide (to undertake the project), Access (changing the metadata), Repair (the label, record, shelving location, etc) or Eliminate (weed)